Background Noise: Perspectives on Sound Art - Labelle, Brandon (London Continuum, 2006)
Background Noise follows the development of sound as an artistic medium and illustrates how sound is put to use within modes of composition, installation, and performance. While chronological in its structure, Brandon LaBelle's book is informed by spatial thinking - weaving architecture, environments, and the specifics of location into the work of sound.